Entrepreneurial Overconfidence: Evidence from a C.A.R.T. Approach - Philipp Köllinger; Maria Minniti; Christian Schade (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
We use a sample of 18 countries to study what variables have a significant impact on an indi-vidual?s decision to start a new business and classification and regression trees for an accurate interpretation of the data. Our results support existing literature suggesting the existence of strong country effects. In addition, we find strong evidence that perceptual variables, such as one?s belief about her own skills and ability and about the risk involved in the venture, have a crucial impact on new business creation across all countries in our sample. Our findings are consistent with the idea that entrepreneurs evaluate their businesses by taking an ?inside view? of their situation, overestimate their likelihood of success, and, as a result, rely signifi-cantly on perceptions rather than on objective expectations of success.
Keywords: D0; J4; 330; CARTs; Entrepreneurship; Overconfidence; Self-Employment